Application of Quality Control in Mobile Digital Radiography and Lead Apron Performance Testing Using CT Scan at West Nusa Tenggara Provincial General Hospital - Baiq Alifa Kanaya Putri; Bayu Septiawan; Lalu Sahrul Hudha (Indonesian Journal of Applied Science and Technology, 2026)
The use of Mobile Digital Radiography (Mobile DR) in radiology services continues to rise due to its flexibility and efficiency; consequently, the implementation of Quality Control (QC) and regular evaluation of radiation protection equipment are necessary to ensure service quality and radiation safety. This study aims to evaluate the implementation of QC on Mobile DR equipment and to assess the suitability of lead aprons using CT scans at the Radiology Department of the NTB Provincial General Hospital. This is a quantitative descriptive study with the research subjects comprising one unit of mobile DR and 13 lead aprons. QC testing was conducted on the parameters of illumination, collimation, and X-ray beam alignment, while the apron suitability test was performed using a 64-slice CT scan to detect lead material leakage. The results showed that the illumination value was 198 lux, collimation was within tolerance limits, and beam alignment was 0°, meaning the Mobile DR unit was deemed to meet suitability standards. Furthermore, 5 out of 13 lead aprons (38.46%) exhibited leakage exceeding tolerance limits and were deemed unfit for use. These findings underscore the importance of implementing quality control (QC) and regular inspections of radiation protection equipment as part of the Quality Assurance programme to ensure the quality of radiology services and radiation safety at the NTB Provincial General Hospital.